Assessing the usability of Accessercise to increase physical activity in adults with physical disabilities: A qualitative think-aloud study - James A. Haley; Daniel J. A. Rhind; David W. Maidment (PLoS ONE, 2025)
Background Mobile health (mHealth) applications (apps) offer a convenient way to increase physical activity to people with disabilities. While several mHealth apps have been developed for this population, there is limited evidence assessing app usability and how this might impact physical activity. Objective To investigate the usability of a novel mHealth app, Accessercise, that aims to increase physical activity in people with physical disabilities. Methods Twelve adults with different physical disabilities participated in a face-to-face think-aloud interview. Interviews were analysed using deductive content analysis based on the User Version of the Mobile Application Rating Scale (uMARS). Findings Data mapped onto 12 uMARS domains; most participants expressed positive views concerning Accessercise, namely, entertainment, customisation, tailoring to the target group, ease of use and navigation, and visual information. Some additional elements were viewed positively but required modification to improve usability, perceived credibility, and relevance, including the app’s layout, visual appeal, interactivity, and quality/quantity of information. Conclusion This study provides an example of how the think-aloud method can be employed to evaluate mHealth apps that aims to increase physical activity in people with physical disabilities. Therefore, developers and researchers could use this study to inform future usability evaluations in this area.